2016
DOI: 10.1111/edt.12282
|View full text |Cite
|
Sign up to set email alerts
|

Superolateral dislocation of an intact mandibular condyle into the temporal fossa: case report and literature review

Abstract: Temporomandibular joint dislocation refers to the dislodgement of mandibular condyle from the glenoid fossa. Anterior and anteromedial dislocations of the mandibular condyle are frequently reported in the literature, but superolateral dislocation is a rare presentation. This report outlines a case of superolateral dislocation of an intact mandibular condyle that occurred in conjunction with an ipsilateral mandibular parasymphysis fracture. A review of the clinical features of superolateral dislocation of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Shen et al22 collected 23 cases of superolateral dislocation (SD) of the mandibular condyle from the literature (1969–2011). Recently, Sharma et al (2016) reported one case of SD 23. The present study reported only eight cases of anterosuperior dislocation of mandibular condyles into the temporal fossa.…”
Section: Case Reportcontrasting
confidence: 48%
See 1 more Smart Citation
“…Shen et al22 collected 23 cases of superolateral dislocation (SD) of the mandibular condyle from the literature (1969–2011). Recently, Sharma et al (2016) reported one case of SD 23. The present study reported only eight cases of anterosuperior dislocation of mandibular condyles into the temporal fossa.…”
Section: Case Reportcontrasting
confidence: 48%
“…Recently, Sharma et al (2016) reported one case of SD. 23 The present study reported only eight cases of anterosuperior dislocation of mandibular condyles into the temporal fossa.…”
Section: Case Reportmentioning
confidence: 61%
“…Early diagnosis is essential to avoid unnecessary intracranial management, but also to ensure that the neurosurgery team is available for a possible craniotomy if there is leakage or bleeding of brain fluid, hematoma, or dural rupture. 5,[7][8][9] The literature mentions that a closed reduction under anesthesia should be considered before an open reduction, especially among young patients. Closed reductions are thought to see more success within between 2 and 4 weeks after the injury, and can minimize growth disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Sociedade Brasileira de Neurocirurgia. All rights reserved.Condylar Dislocation for Intracranial Fossa: a Review Rodrigues and Nascimento achieved by the options of open manipulation, condylectomy, and condylotomy, usually depending on the extent of the lesion 4,8.…”
mentioning
confidence: 99%
“…Temporomandibular dislocation is a dislodgement of the head of the mandibular condyle from its normal position in the glenoid fossa [1]. Temporomandibular dislocations can be classified into different types depending on the direction taken by the condyles out of the glenoid cavity [2].…”
Section: Introductionmentioning
confidence: 99%